Outcome of surgical management of ruptured Achilles tendon - Acharya, Balakrishnan M; Devkota, Pramod; Shrestha, Amrit; Thakur, Abhishek Kumar; Bhatta, Toya Raj; Gyawali, Bidur (Journal of Patan Academy of Health Sciences, 2018)
Introductions: The incidence of Achilles tendon rupture has been increasing worldwide. The optimal management of this problem is controversial but the surgical intervention is being applied widely. Methods: We retrospectively analyzed patients who had Achilles tendon (AT) rupture treated surgically at Patan Academy of Health Sciences from January 2010 to December 2015. Functional outcome assessment of ankle was done by using American Orthopedic foot and Ankle Society Score (AOFAS). Results: Total 71 patients (male 45, female 26) had surgery for AT, 38 right and 33 left side. The mean age of the patient was 36.14 years (range 18-67 years). The mean AOFAS score was 83.32 (range 75-93) after first year follow up and 90.36 (range 80-99) after second year, difference was statistically significant (p<0.05). Conclusions: The study showed high AOFAS score for surgical management of ruptured Achilles tendon.